Sustainability of African smallholder farming systems: case study of highland areas of Central Africa - Manyong, A.M.; Degand, J. (Informa UK Limited, 1995)
This article shows that the measurement of the sustainability of a production system should be conducted using a systems approach which corresponds best with the social, economic and bio-physical parameters of the African smallholder farming system. The case study shows that the system as a whole is not sustainable, that improvements would be possible if the system were made more efficient, and that it is vital to introduce new technologies if complete sustainability is the ultimate aim. It would be better to analyse the concept of sustainability at the community level, rather than at the level of the individual farmer. Multiple-objective mathematical programming models are appropriate to address such issues.